Groove Pancreatitis with Biliary and Duodenal Stricture: An Unusual Cause of Obstructive Jaundice - Gravito-Soares,Marta (2016)
Introduction: Groove pancreatitis is an uncommon cause of chronic pancreatitis that affects the groove anatomical area between the head of the pancreas, duodenum, and common bile duct. Clinical case: A 67-year-old man with frequent biliary colic and an alcohol consumption of 30-40 g/day was admitted to the hospital complaining of jaundice and pruritus. Laboratory analysis revealed cholestasis and the ultrasound scan showed intra-hepatic biliary ducts dilatation, middle third cystic dilatation of common bile duct, enlarged Wirsung and pancreatic atrophy. The magnetic resonance cholangiopancreatography showed imaging findings compatible with groove pancreatitis. An esophagogastroduodenoscopy later excluded duodenal neoplasia. He was submitted to a Roux-en-Y cholangiojejunostomy because of common bile duct stricture. Five months later a gastrojejunostomy was performed due to a duodenal stricture. The patient remains asymptomatic during follow-up. Discussion: Groove pancreatitis is a benign cause of obstructive jaundice, whose main differential diagnosis is duodenal or pancreatic neoplasia. When this condition causes duodenal or biliary stricture, surgical treatment can be necessary.